PROBLEMATIKA PENALARAN CHATGPT DALAM MENYELESAIKAN SOAL KOMBINATORIKA [THE PROBLEMATIC REASONING OF CHATGPT IN SOLVING COMBINATORICS PROBLEMS] - Rofiki, Imam; Dewi, Aulia Rahma (JOHME: Journal of Holistic Mathematics Education, 2024)
The development of the digital era in the 21st century has brought significant changes in various aspects of human life, especially education. Technologies such as artificial intelligence (AI) have been applied in various fields, including education, to improve the efficiency and effectiveness of learning. ChatGPT, one of the text-based AI models, is used to answer various user questions. This study aims to analyze ChatGPT's problematic reasoning in solving combinatorics problems. The research method used is qualitative with a case study design. Data were collected through a test and interview (questions and answers) to ChatGPT version 3.5. The results showed that ChatGPT's problems were errors in calculating the number and position of letters, as well as inconsistency in the answers given. Although ChatGPT can provide explanations of basic concepts in combinatorics, ChatGPT has limitations in in-depth reasoning and lacks precise calculation accuracy. In fact, ChatGPT was unable to answer the questions clearly. This shows that ChatGPT lacks reasoning towards solving combinatorics problems. Users need to evaluate and verify the responses/answers given by ChatGPT.BAHASA INDONESIA ABSTRACT: Perkembangan era digital pada abad ke-21 telah membawa perubahan signifikan dalam berbagai aspek kehidupan manusia, khususnya bidang pendidikan. Teknologi seperti kecerdasan buatan/artificial intelligence (AI) telah diterapkan dalam berbagai bidang, termasuk pendidikan, untuk meningkatkan efisiensi dan efektivitas pembelajaran. ChatGPT, sebagai salah satu model AI berbasis teks, digunakan untuk menjawab berbagai pertanyaan pengguna. Penelitian ini bertujuan untuk menganalisis problematika penalaran ChatGPT dalam menyelesaikan soal-soal kombinatorika. Metode penelitian yang digunakan adalah kualitatif dengan desain studi kasus. Data dikumpulkan melalui tes dan wawancara (tanya jawab) terhadap ChatGPT versi 3.5. Hasil penelitian menunjukkan bahwa problematika ChatGPT adalah kesalahan dalam perhitungan jumlah dan posisi huruf, serta ketidakonsistenan dalam jawaban yang diberikan. Meskipun, ChatGPT mampu memberikan penjelasan konsep dasar dalam kombinatorika, tetapi ChatGPT memiliki keterbatasan dalam penalaran mendalam dan tidak memiliki akurasi perhitungan yang tepat. Bahkan ChatGPT tidak dapat menjawab soal yang diberikan secara jelas. Hal ini menunjukkan bahwa ChatGPT memiliki penalaran yang kurang terhadap penyelesaian soal kombinatorika. Pengguna perlu untuk melakukan evaluasi dan verifikasi respons/jawaban yang diberikan oleh ChatGPT.